2016
DOI: 10.1016/j.jinteco.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Importing, exporting, and firm-level employment volatility

Abstract: In this paper, we use detailed trade and transactions data for the U.S. manufacturing sector to empirically analyze the direction and magnitude of the association between firm-level exposure to trade and the volatility of employment growth. We find that, relative to purely domestic firms, firms that only export and firms that both export and import are less volatile, whereas firms that only import are more volatile. The positive relationship between importing and volatility is driven mainly by firms that switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 28 publications
8
56
0
Order By: Relevance
“…32 Another branch of literature on the diversification of risk has studied whether firms using complex production structures with several intermediates could be less volatile (Koren and Tenreyro (2013)). Kurz and Senses (2013) establish that firms with substantial imports and exports have lower employment volatility than domestic firms in the medium to long term, which they attribute partly to the diversification of risk. 33 The key result in this paper points to a possibly overlooked fact: the extent of the benefits from diversification depends heavily on the substitutability of inputs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…32 Another branch of literature on the diversification of risk has studied whether firms using complex production structures with several intermediates could be less volatile (Koren and Tenreyro (2013)). Kurz and Senses (2013) establish that firms with substantial imports and exports have lower employment volatility than domestic firms in the medium to long term, which they attribute partly to the diversification of risk. 33 The key result in this paper points to a possibly overlooked fact: the extent of the benefits from diversification depends heavily on the substitutability of inputs.…”
Section: Discussionmentioning
confidence: 97%
“…See Peek and Rosengren (1997) and Peek and Rosengren (2000) for the case of U.S. affiliates from Japan. 33 An interesting result from Kurz and Senses (2013) is that firms that only import are actually more volatile than the domestic-only benchmark.…”
Section: Discussionmentioning
confidence: 99%
“…Kurz and Senses (2016) competition and find that increased import competition has a substantial positive causal effect on labor income risk. In an extension they include a measure for industry-level offshoring and find that an increase in offshoring is associated with a decline in income risk.…”
Section: Empirics On Offshoring Labor Demand Elasticities and Volatimentioning
confidence: 99%
“…Several studies have shown that variability in exchange rates has a significant impact on the variability of US employment and wages [3], [4]. Another study also empirically documents the link between firms' openness to trade and employment volatility [5]. Employment variability is mainly driven by variability in job flows, namely job creation and destruction.…”
Section: Impact Of Exchange Rates On Firms' Competitivenessmentioning
confidence: 99%